Radiation‐Tolerant Electronic Devices Using Wide Bandgap Semiconductors. Issue 2 (30th September 2022) - Muhammad, Zahir; Wang, Yan; Zhang, Yue; Vallobra, Pierre; Peng, Shouzhong; Yu, Songyan; Lv, Ziyu; Cheng, Houyi; Zhao, Weisheng
Abstract: The aspiration of electronic technologies that are resistant to high‐energy cosmic radiation is essential for current harsh radiation environment exploration. Integrated circuits mostly require post‐processing after designing, making their structures more complex than the standard systems. Thus, unique designs and strategies are developed to enable the high tolerance of space electronics to radiation in nuclear and avionic applications. The wide bandgap semiconductor (WBG) materials with excellent electronic/optical properties and structural stability are appealing options for radiation‐immune applications. Here, in this article, the development and fabrication of various electronic devices have been reviewed using different wide bandgap materials for radiation‐hardened applications. Detailed investigations are discussed, from the fundamental wide bandgap materials withstanding limited irradiation to the development processes of the electronic devices used in harsh environments. Furthermore, the challenges and future perspectives of the WBG‐based radiation harsh electronic devices are also highlighted in this review with commercial application in space stations and aircraft. Abstract : To design the integrated circuits, it is really important to be rad‐hard, which is the most challenging research and hot area for the researcher and industries to find the best candidates as well the fabrication techniques in this current radiation‐hard environment. Wide bandgap semiconductors‐based devices can drive the radiation‐hardened integrated circuit technologies and memory design for a high radiation environment.